2005
DOI: 10.1093/gerona/60.7.815
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Characteristics Change With Aging: Role of Estrogen Receptor  

Abstract: Estrogen receptor beta (betaER) is the predominant estrogen receptor in platelets. Experiments were designed to define phenotypic changes in platelets with aging following deletion of betaER (betaERKO). Blood was collected from wild-type and betaERKO female mice at 4-7 (young) and 24-25 (aged) months of age. In young animals, total number of platelets, number of platelets containing RNA (reticulated platelets), aggregation, dense body adenosine triphosphate secretion, and alpha granular secretion were the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 29 publications
4
26
1
1
Order By: Relevance
“…Notably, ATP concentration in trophocytes and fat cells have also been shown to decrease with advancing age in worker bees reared in a thermostatic chamber at 34°C (Hsu and Chan 2011a), providing further support for the idea that young and old workers reared in a field hive can be used for studying aging. This decrease in ATP concentration in trophocytes and fat cells of older workers is also consistent with previous studies showing that ATP levels decrease with advancing age in the gastric mucosa and muscle of humans (Kawano et al 1991;Conley et al 2000;Petersen et al 2003;Gurd et al 2008), the blood and brains of mice (Jayachandran et al 2005;Joo et al 1999), the erythrocytes of rabbits (Subasinghe and Spence 2008) and cows (Bartosz et al 1982), and the hearts of rats (Guerrieri et al 1996). This finding is also consistent with the results of ΔΨm measurements reported in this study; as was the case for NAD + , a decrease in ΔΨm can result in a decrease in ATP concentration.…”
Section: δψMsupporting
confidence: 92%
“…Notably, ATP concentration in trophocytes and fat cells have also been shown to decrease with advancing age in worker bees reared in a thermostatic chamber at 34°C (Hsu and Chan 2011a), providing further support for the idea that young and old workers reared in a field hive can be used for studying aging. This decrease in ATP concentration in trophocytes and fat cells of older workers is also consistent with previous studies showing that ATP levels decrease with advancing age in the gastric mucosa and muscle of humans (Kawano et al 1991;Conley et al 2000;Petersen et al 2003;Gurd et al 2008), the blood and brains of mice (Jayachandran et al 2005;Joo et al 1999), the erythrocytes of rabbits (Subasinghe and Spence 2008) and cows (Bartosz et al 1982), and the hearts of rats (Guerrieri et al 1996). This finding is also consistent with the results of ΔΨm measurements reported in this study; as was the case for NAD + , a decrease in ΔΨm can result in a decrease in ATP concentration.…”
Section: δψMsupporting
confidence: 92%
“…ATP concentration decreases with age in the gastric mucosa and muscle of humans (Kawano et al 1991;Gurd et al 2008), the blood and brain of mice (Jayachandran et al 2005;Joo et al 1999), the erythrocytes of rabbits (Subasinghe and Spence 2008) and cows (Bartosz et al 1982), and the heart of rats (Guerrieri et al 1996). Similarly, we have found that ATP concentration decreases with age in the trophocytes and oenocytes of worker bees (Hsu and Chan 2013;Chuang and Hsu 2013).…”
Section: Nad + Nadh and Atp Concentrationssupporting
confidence: 66%
“…Although age is a well-known cardiovascular risk factor (Vokonas et al 1988), studies examining the direct effects of aging on platelet functioning have yielded heterogeneous results (Vericel et al 1988;Jayachandran et al 2005). Knight et al (1997) found age was associated with decreased PSEL platelet activity, while the current study did not find any significant association between age and platelet responses to acute stress.…”
Section: Discussioncontrasting
confidence: 56%